Specific features of the clinical course and chemotherapy of tuberculosis in children exposed to tuberculosis with different drug resistance patterns - M. E. Lozovskaya; A. S. Kurova; E. B. Vasilieva; L. V. Klochkova; N. A. Nikiforenko; A. V. Mosina (Туберкулез и болезни лёгких)
The objective: to characterize tuberculosis in children exposed todrug-resistant tuberculosis in St. Petersburg.Subjects and methods. 51 children exposed to tuberculosis in their families were enrolled into the study; of them, 23 children were exposed to MDR TB; 7 children were exposed to other drug resistant patterns of the disease; 21 children were exposed to drug susceptible tuberculosis.Results. In St. Petersburg in 2015-2017, MDR TB cases prevailed among adult index cases to whom children were exposed. The course of tuberculosis was the most severe in children exposed to MDR TB. Such children were treated with regimen IV with high eﬃcacy achieved, taking into account the severity of the disease, age, concurrent disorders, and tolerability of the drugs, as well as drug resistance of the index case.